Răspuns :
2 * {[(3 * 5^2 - 2^3 * 18 : 3^2 + 3 * 11) : 2^2] + 6}
= 2 * {[(3 * 25 - 2^3 * 18 : 3^2 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 2^3 * 18 : 3^2 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 2^3 * 18 : 9 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 2^3 * 2 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 8 * 2 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 16 + 3 * 11) : 2^2] + 6}
= 2 * {[(75 - 16 + 33) : 2^2] + 6}
= 2 * {[(59 + 33) : 2^2] + 6}
= 2 * (92 : 2^2 + 6)
= 2 * (92 : 4 + 6)
= 2 * (23 + 6)
= 2 * 29
= 58
-
Sper ca te-am ajutat! :D